Thursday
March 23, 2017

Post a New Question

Posted by on Tuesday, June 17, 2014 at 9:04pm.

Find the value of x so that 3x – 2, 2x – 1 and 4x – 3 form an arithmetic sequence.

  • Math - , Tuesday, June 17, 2014 at 9:32pm

    It must be true that

    (2x-1) - (3x-2) = (4x-3) - (2x-1)
    -x + 1 = 2x - 2
    -3x = -3
    x = 1

    check:
    terms would be
    1 , 1, 1
    strange sequence but it is arithmetic

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question